PENGEMBANGAN KECERDASAN EMOSIONAL ANAK MELALUI METODE MAIN PERAN DI KB AL HASYIMI II SIDOARJO - ANIS SYA'ADAH ANIS (Universitas PGRI Palembang, 2023)
The aim of this research is to determine the development of children's emotional intelligence through the role-playing method. This research uses a qualitative descriptive type of research, where everything is explained according to events in the field. The main subjects in this research were 3 colleagues or teachers and 15 young children. Data collection techniques use interviews and observation. When children play roles with a certain theme, children are also learning something by playing in a fun way. Share information and experiences. And also learn to socialize with the environment, friends and circumstances. Keywords: Emotional Intelligence; Role Playing; Early childhood